Silence at Boalt Hall : The Dismantling of Affirmative Action - Guerrero, Andrea, 1970- (Book collections on Project MUSE., 2002)
In 1995, in a marked reversal of progress in the march toward racial equity, the Board of Regents voted to end affirmative action at the University of California. One year later the electorate voted to do the same across the state of California. Silence at Boalt Hall is the thirty-year story of students, faculty, and administrators struggling with the politics of race in higher education at U.